Pengaruh Pembelajaran Inkuiri Terbimbing terhadap Kemampuan Berpikir Kritis IPA Peserta Didik: inquiry learning model, critical thinking, science learning. - Ranti, Sofia; Dwi Kurino, Yeni (Papanda Journal of Mathematics and Science Research, 2023)
This study aims to determine the effect of the inquiry learning model on students' natural science critical thinking skills. This study uses the SLR (Systematic Literature Review) method. Sources of data obtained from various articles and research journals. Data collection was carried out by reviewing all articles related to the use of the Inquiry learning model published in the 2018-2022 period. The articles used in this study were 15 articles obtained from DOAJ and Google Scholar using the Publish or Perish application. Each article was recorded and then classified based of year of study, level of class, and research method to be analyzed one by one. The results of this SLR show that most research on the implementation of the Inquiry learning model on students' critical thinking skills was carried out in 2020 and the most research subjects were elementary school students with the most widely used research method being the quantitative method (Quasi Experiment) and in general the results show that the Inquiry model is able to provide positive impact compared to other learning models. The results of this study can be a consideration for researchers in conducting research and for teachers in conducting learning activities in class